Phase synchronous inverter for microgrid system - Rahman, Tawfikur; Motakabber, S. M. A.; Ibrahimy, Muhammad Ibn (The Institute of Electrical and Electronics Engineers, Inc., 2016)
The synchronous inverter is an electrical inverter device which is synchronizing inverter phase into the microgrid phase at the same amplitude and frequency. A three phase phase synchronous inverter (PSI) is basically used in the high efficiency power supply systems. The inverter phase is depend on the controllers which are two level pulse width modulation (PWM) generator, phase lock loop (PLL) regulator, DC voltage regulator current regulator and Uref generator to get the reference input and output voltage and current for synchronizing the phase angle. An inverter using a three leg IGBT has been designed for microgrid systems and simulated by using MATLAB2014a. The input and output lowpass LC filters are used to synchronize the micro-grid phase. The controllers have generated PWM signal and a zero crossing sampling is used to precisely synchronize with microgrid line frequency. A balanced microgrid load of star configuration (00, 1200 and -1200 degree), and also the input DC voltage ± 250V are considered in this design. The overall conversion efficiency of the PSI is 97.62% and phase synchronization error for each phase is about 0.50, 1540 and 2650 degrees. The results show that the design has better performance and can be used efficiently in the micro-grid system.